Development the Ability to Create Stories and Puppets for Early Childhood Education Students Using STEM Education Concepts - Rewchaiochot, Kaewta (Rajapark Journal, 2024)
This research is quasi-experimental research conducted with multiple data collections over different periods, employing a One Group Time-Series Design. The objectives were to 1) determine the effectiveness of the STEM education-based learning management plan, 2) compare students' abilities in stories and puppet creation before and after receiving STEM education-based learning management, and 3) investigate students' satisfaction with STEM education-based learning management. Participant was obtained through simple random sampling, using classes as the sampling units. The research instruments included: 1) a STEM education-based learning management plan for the subject of storytelling and puppetry for early childhood, 2) an assessment form for the ability to create stories and puppets for early childhood, and 3) a satisfaction assessment form for STEM education-based learning management. Data were analyzed using mean, standard deviation, and t-test for dependent samples. The research findings are as follows: 1) the effectiveness index of the learning management plan is 76.80%, 2) students' abilities in stories and puppet creation after receiving STEM education-based learning management are significantly higher than before at the .05 level (Z=416, p < .001), and 3) the overall satisfaction with STEM education-based learning management is at the highest level (x = 4.66, SD = 0.45).